Edukasi Si Gulatus: Siaga Gula dan Lawan Ancaman Diabetes Melitus - Firmansyah Firmansyah; Amanda Khaerani Salsabella; Alya Nida Tendyansyah (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Diabetes Mellitus (DM) is a chronic disease caused by insulin hormone disruption, which is closely related to lifestyle and dietary habits. Health education is highly necessary to increase knowledge that serves as a foundation for altering patients' daily behaviors. This community service utilized education and capacity-building methods through the "Si Gulatus" program counseling, alongside a cooking demonstration of fruit getuk made from local cassava. The activity involved 22 participants from the elderly women's group at Aisyiyah PRA Karangasem. The program's success was evaluated using pre-test and post-test questionnaires consisting of 20 questions. The results showed a significant improvement in the participants' understanding of diabetes management. Quantitatively, the participants' average pre-test score was 82, which increased to an average of 88 in the post-test. As an operational recommendation, a structured and sustainable approach is essential to assist participants in implementing dietary management and food selection knowledge into their daily lives.